1983
DOI: 10.1029/ja088ia11p09163
|View full text |Cite
|
Sign up to set email alerts
|

Are equatorial electron cyclotron waves responsible for diffuse auroral electron precipitation?

Abstract: On the basis of theoretical calculations of electron diffusion coefficients and of OGO 5 data, Lyons [1974] suggested that electrostatic electron cyclotron harmonic waves had amplitudes large enough to cause the strong pitch angle diffusion of plasma sheet keV electrons and to be responsible for diffuse auroral precipitation. However, recent measurements of the wave location and amplitude performed aboard the GEOS spacecraft have brought new pieces of information challenging these conclusions. Our calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
80
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 25 publications
4
80
0
Order By: Relevance
“…The alternative theory is electron scattering by whistler mode waves (Kennel et al, 1970;Lyons, 1974;Horne and Thorne, 2000). The main argument against the first theory has been that the power of the ECH waves measured at geostationary orbit is not sufficient to cause strong pitch angle diffusion (Belmont et al, 1983).The main problem with the second mechanism was that, although Johnstone et al (1993) showed that whistler mode waves can resonate with keV electrons in the frequency band below the electron gyro frequency, relatively high temperature anisotropies are required to generate such waves. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The alternative theory is electron scattering by whistler mode waves (Kennel et al, 1970;Lyons, 1974;Horne and Thorne, 2000). The main argument against the first theory has been that the power of the ECH waves measured at geostationary orbit is not sufficient to cause strong pitch angle diffusion (Belmont et al, 1983).The main problem with the second mechanism was that, although Johnstone et al (1993) showed that whistler mode waves can resonate with keV electrons in the frequency band below the electron gyro frequency, relatively high temperature anisotropies are required to generate such waves. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1970s, the calculations of pitch angle scattering rate [Lyons,1974] based on the initial OGO-5 wave observations [Kennel et al, 1970] indicated that the amplitudes of ECH waves are large enough to scatter the electrons with energies from a few hundred eV to several keV, suggesting that the ECH waves are responsible for the loss of the plasma sheet electrons. However, in the 1980s, statistical surveys of occurrence rate of ECH waves indicated that the amplitude of ECH waves rarely have the sufficient power to scatter the plasma sheet electrons [e.g., Belmont et al, 1983;Roeder and Koons, 1989]. The new calculation of pitch angle diffusion done by Horne and Thorne [2000] suggested that the ECH waves can scatter the plasma sheet electrons when the waves lie the favored frequency ranges.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the wave-particle interactions are an important loss mechanism of the plasma sheet electrons. Both electron cyclotron harmonic (ECH) waves and the whistler mode chorus resonate with the plasma sheet electrons [Horne et al, 2003a], and the main contributor of the diffuse aurora (i.e., sweeper of the plasma sheet electrons) has been discussed by many researchers, but it is still a subject of controversy in magnetospheric physics [e.g., Belmont et al, 1983;Roeder and Koons, 1989;Horne and Thorne, 2000;Ni et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, by studying the formation of pancakes, we may also be able to derive important information on the origin of the diffuse aurora., a problem which has been the subject of considerable controversy [e.g., Belmont et al, 1983Belmont et al, , 1984Lyons, 1984;Schumaker et al, 1989;Roeder and Koons, 1989] and which remains unresolved [Koskinnen, 1997].…”
Section: Introductionmentioning
confidence: 99%